Pengaruh Pengetahuan Tentang Laporan Keuangan Terhadap Minat Mahasiswa dalam Berinvestasi Saham dengan Preferensi Risiko Sebagai Variabel Moderasi - Dewi Kusuma Wardani; Agustin Dwi Hapsari (Jurnal Simki Economic, 2022)
This study was conducted with the aim of testing the relationship between knowledge of financial statements and student interest in investing in stocks with risk preference as a moderating variable. The data in this study were obtained from 100 respondents from accounting students of the Faculty of Economics, Sarjanawiyata Tamansiswa University using quantitative description methods and primary data in the form of questionnaires. The sample in this study was obtained using a snowball sampling technique. The result of this research is that knowledge about financial statements has an effect on increasing student interest in investing in stocks.